Nitric Oxide Synthase Type 1 Methylation Is Associated With White Matter Microstructure in the Corpus Callosum and Greater Panic Disorder Severity Among Panic Disorder Patients - Xu, Huazhen; Zhong, Yuan; Yuan, Shiting; Wu, Yun; Ma, Zijuan; Hao, Ziyu; Ding, Huachen; Wu, Huiqing; Liu, Gang; Pang, Manlong; Liu, Na; Wang, Chun; et al. (Frontiers in Neurology, 2021)
Objectives: Methylation of the neuronal nitric oxide synthase (NOS1/nNOS) gene has recently been identified as a promising biomarker of psychiatric disorders. NOS1 plays an essential role in neurite outgrowth and may thus affect the microstructure development of white matter (WM) in the corpus callosum (CC), which is known to be altered in panic disorder (PD). We examined the relationship between NOS1 methylation, WM tracts in the CC, and symptoms based on this finding. Methods: Thirty-two patients with PD and 22 healthy controls (HCs) were recruited after age, gender, and the education level were matched. The cell type used was whole-blood DNA, and DNA methylation of NOS1 was measured at 20 CpG sites in the promoter region. Although 25 patients with PD were assessed with the Panic Disorder Severity Scale (PDSS), diffusion tensor imaging (DTI) scans were only collected from 16 participants with PD. Results: We observed that the PD group showed lower methylation than did the HCs group and positive correlations between the symptom severity of PD and methylation at CpG4 and CpG9. In addition, CpG9 methylation was significantly correlated with the fractional anisotropy (FA) and mean diffusivity (MD) values of the CC and its major components (the genu and the splenium) in the PD group. Furthermore, path analyses showed that CpG9 methylation offers a mediating effect for the association between the MD values of the genu of the CC and PD symptom severity (95% CI = −1.731 to −0.034). Conclusions: The results suggest that CpG9 methylation leads to atypical development of the genu of the CC, resulting in higher PD symptom severity, adding support for the methylation of NOS1 as a future prognostic indicator of PD.